Analisis Pemahaman Siswa dalam Menyelesaikan Soal Berbasis Literasi Matematis - Cahyanti, Citra; Putra, Eric Dwi; Murtinasari, Frida (Media Pendidikan Matematika, 2025)
This study aims to investigate the extent to which students comprehend and solve problems grounded in mathematical literacy. This research adopts a descriptive method with a qualitative approach to portray students’ comprehension in addressing mathematical literacy tasks. Students’ understanding is analyzed based on three indicators proposed by Ruseffendi: translation, interpretation, and extrapolation. The data collection techniques employed in this study include written tests and interviews. The written test is used to assess students’ mastery of the material, while interviews are conducted with selected participants to gain deeper insight into how they comprehend and solve the given problems. The study was conducted at SMP Lab Jenggawah, involving four student participants—two identified as having high mathematical ability and two with low mathematical ability. Students with high mathematical ability exhibited a strong level of comprehension, as demonstrated by their achievement across all three indicators: translation, interpretation, and extrapolation. Conversely, students with low mathematical ability tended to display limited comprehension, as they were only able to reach the levels of translation and interpretation, without attaining the extrapolation stage. Students with lower levels of mathematical ability encountered challenges such as limited comprehension of the contextual aspects of literacy-based problems and inaccuracies in performing calculations, especially at the extrapolation stage. These findings underscore the necessity of reinforcing instructional strategies that effectively foster mathematical literacy, with adaptations aligned to students’ varying levels of proficiency.